EKSISTENSI ROADSTEADS DAN PEMANFAATAN HAK EKONOMI DI LAUT - Marlina, Marlina (Faculty of Law, University of Muhammadiyah Malang, 2017)
Roadsteads are part of the territorial sea. The function of Roadsteads in the utilization of economic rights at sea lies in the purpose of keeping in the form of surveillance, prevention of violations and law enforcement in the territorial sea. By default the setting of the 12-mile freeway is an additional zone where special and limited jurisdiction is applicable. So the role for keeping purpose can still be applied in the zone. While on the purpose of managing the fields in ZEE and LK then the existence of Roadsteads as facilities provided by the State coast as one form of temporary arrangement. This form of provisional arrangement is directed at the sustainable use of economic rights. UNCLOS stipulates that temporary, practical arrangements can be taken in the event that there are slices in ZEE and LK between two opposing and contiguous States. Where the utilization of economic rights at sea that provides opportunities to other countries are in space ZEE and LK. The room where there are many violations due to the unfinished issue of mutually agreed limitations. The existence of Roadsteads is able to answer the pattern of maintaining and managing related to the utilization of economic rights at sea. Through library search and related rules, the author tries to provide conceptual answers in the study of Roadsteads and the utilization of economic rights at sea.